How Did We Deliver Team-Based Learning (TBL) Remotely to Overcome Digital Divide and Internet Access Inequality? - AlZaabi, Adhari (International Journal of Emerging Technologies in Learning (iJET), 2023)
The shift to online learning during COVID-19 has uncovered the existing internet access inequality in the world. Shifting an interactive team-based learning (TBL) session to online is even more challenging since it necessitates interactions and feedback. Choosing the proper digital platforms for online TBL is critical to ensure achieving the intended benefits of TBL. A face-to-face TBL course was transformed fully to online. The basic TBL elements, i.e., pre-reading materials, iRAT, tRAT, and the tAPPS, remained the same in online TBL. Platforms that use less internet bandwidth and are familiar to students were used such as Google meet, WhatsApp, and Google Chat. An online questionnaire was disseminated to all students at the end of the semester to get their feedback. Sixty-six students responded to the questionnaire (54% response rate). The majority of the students (85%) perceived the online TBL positively and reported good interaction and engagement without any major technical issues. They reported that the application exercises and the online discussion through WhatsApp and the use of emoji have helped them to interact and comprehend the topics. Therefore, the use of technologies that operate at low internet bandwidth is an option to provide an equitable access to active learning.